2011
DOI: 10.1093/ecam/nep142
|View full text |Cite
|
Sign up to set email alerts
|

Alpinia pricei Rhizome Extracts Induce Cell Cycle Arrest in Human Squamous Carcinoma KB Cells and Suppress Tumor Growth in Nude Mice

Abstract: Alpinia pricei has been shown to induce apoptosis in human squamous carcinoma (KB) cells. In this study, we report the effectiveness of the ethanol (70%) extracts of A. pricei rhizome (AP extracts) in terms of tumor regression as determined using both in vitro cell culture and in vivo athymic nude mice models of KB cells. We found that the AP extract (25–200 μg/mL) treatment decreased the proliferation of KB cells by arresting progression through the G2/M phase of the cell cycle. This cell cycle blockade was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…The 70% ethanol was capable to extract the flavonoid as the important compounds in propolis. The 70% ethanol is semipolar solvent which can extract all active components with different polarity in the propolis (Cunha et al, 2004;Hasan et al,2006) and the optimum conditions for extracting flavonoid for Alpinia pricei rhizome (Hseu et al, 2011).…”
Section: Results and Discussion Propolis Extractionmentioning
confidence: 99%
“…The 70% ethanol was capable to extract the flavonoid as the important compounds in propolis. The 70% ethanol is semipolar solvent which can extract all active components with different polarity in the propolis (Cunha et al, 2004;Hasan et al,2006) and the optimum conditions for extracting flavonoid for Alpinia pricei rhizome (Hseu et al, 2011).…”
Section: Results and Discussion Propolis Extractionmentioning
confidence: 99%
“…Metastasis of tumor cells involves multiple processes and various cytophysiological changes, including changes in adhesion between cells and the extracellular matrix that leads abnormal intercellular interactions (Hseu et al, 2009). Thus, the degradation of ECM and components of the basement membrane, caused by the concerted action of proteinases, such as PA and MMPs, plays a critical role in tumor invasion and metastasis (Hseu et al, 2009;Kessenbrock et al, 2010). Among these enzymes, MMP-9, MMP-2, and u-PA that degrade the basal membrane components and are known to be deeply involved in cancer metastasis (Yang et al, 2005;Hseu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the degradation of ECM and components of the basement membrane, caused by the concerted action of proteinases, such as PA and MMPs, plays a critical role in tumor invasion and metastasis (Hseu et al, 2009;Kessenbrock et al, 2010). Among these enzymes, MMP-9, MMP-2, and u-PA that degrade the basal membrane components and are known to be deeply involved in cancer metastasis (Yang et al, 2005;Hseu et al, 2009). Therefore, the inhibition of migration/invasion mediated by MMPs and/or u-PA could be a potential method to prevent or inhibit cancer metastasis (Bjorklund and Koivunen, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that HeLa cell line marker chromosomes have identified in the KB cell line, and through DNA fingerprinting, KB cells are now thought to have been produced due to HeLa cell contamination. 3 Myrmecodia tuberosa (M. tuberosa) are plants that are attached to other plants (epiphyte) and thrived in the highlands of Wamena, Papua, Indonesia. Originally, M. tuberosa was introduced in the inland of Papua, and commonly used as a medicine by local residents.…”
Section: Introductionmentioning
confidence: 99%